Corrosion and wear resistant brake discs and related methods
By electrodepositing and precipitating hardened cobalt-phosphorus alloy coating on the surface of the brake disc, combined with heat treatment and machining technology, the problems of brake disc material wear and corrosion are solved, and efficient wear and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411268363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-11
- Publication Date
- 2025-04-04
AI Technical Summary
The existing brake disc material is prone to wear and corrode, and the protective coating is prone to peel off, resulting in premature wear of the brake assembly and difficult to maintain corrosion resistance in humid climates.
Electrodeposition technology is used to deposit and deposit hardened cobalt-phosphorus (CoP) alloy coating on the brake surface, and combined with heat treatment and machining technology to form a wear-resistant coating with high Vickers hardness.
The wear resistance and corrosion resistance of the brake disc are achieved, the bond strength between the coating and the substrate material is significantly improved, and post-machine is allowed in the pre-hardened state, extending the service life of the brake assembly.
Smart Images

Figure CN119755222A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to brake assemblies and, more particularly, to corrosion- and wear-resistant brake discs having a precipitation-hardened protective coating on the braking surface and methods of making the same. Background Art
[0002] Disc brake systems are widely used in a variety of vehicles and typically include a caliper that is used to accommodate and press / squeeze (e.g., via a master cylinder) one or more pads against a brake disc (or "rotor") that is fixed to a shaft (e.g., an axle). This interaction creates friction and is used to slow, stop, or arrest the rotation of the shaft ("braking"). The brake disc typically includes an annular structure ("brake band") that includes a braking surface against which the pads are pressed during braking and a central fixed element ("bell" or "hub") that is adapted to hold and fix the disc to the rotating shaft of the vehicle. Typically, the brake band is provided with a pair of opposing braking surfaces that are configured to be engaged by a pair of opposing brake pads within a caliper that is fixed to a non-rotating component of the vehicle. The controlled interaction between the brake pads and the braking surfaces of the brake band provides a braking action via friction, thereby allowing the vehicle to be slowed or stopped.
[0003] Generally speaking, brake discs are made of grey cast iron or steel, which are chosen because of their low cost and acceptable braking performance and wear. However, these materials are heavy, prone to wear, resulting in frequent maintenance and / or replacement requirements, and are additionally susceptible to excessive surface oxidation and rust. These issues can affect both the appearance as well as the performance of the brake disc. In addition, there are increasing environmental concerns regarding brake dust, i.e., iron particles generated by the grinding of cast iron brake discs by associated brake pads. It is estimated that brake dust contributes approximately 20% of the fine particulate matter pollution of current motor vehicles, compared to a contribution of approximately 7% from exhaust gases, and is associated with a variety of aerosol-related respiratory problems. As a result, many environmental and legal initiatives have been proposed to reduce or eliminate brake systems that form brake dust.
[0004] Research into alternative materials has been mixed. Discs made from titanium, carbon or carbon ceramic materials offer improved performance in terms of braking, reduced weight and reduced wear. However, these materials are only available at a much higher cost and have not been widely adopted. In order to reduce the weight of the disc, aluminum discs have been proposed as a cheap alternative to gray cast iron discs or steel discs. Such aluminum discs have a protective coating to reduce disc wear and protect the aluminum substrate from the temperatures generated during braking, which are generally well above the softening temperature of aluminum (200°C to 400°C). Similar cast iron coated discs have also been studied in order to simply reduce wear and surface oxidation of the widely used disc material.
[0005] Unfortunately, despite providing varying degrees of wear resistance, the protective coatings currently applied to aluminum, cast iron or steel discs typically flake off, resulting in detachment from the disc itself and ultimately premature wear of the associated brake components. Various technologies have been explored to address this problem, with manufacturers and developers relying on well-known coating and deposition procedures, including high velocity oxygen fuel (HVOF) technology, high velocity air fuel (HVAF) technology, and kinetic metallization (KM) technology. A combination of HVOF deposition technology, HVAF deposition technology, and KM deposition technology typically provides a protective coating with increased bond strength, which provides a higher anchoring capability on a gray cast iron substrate or steel substrate. However, while such methods can significantly reduce the flaking of the protective coatings produced, none of the methods can eliminate the problem, or address the additional issues regarding corrosion resistance, which is necessary in wet climates, particularly in areas where salt is used to control road conditions such as icing.
[0006] Additionally, in addition to ongoing performance issues, modern protective coatings and application techniques are expensive and provide applied coatings in a hard and brittle state. The latter issue hinders post-coating machining or surface finishing, resulting in the need for strict process control to ensure that appropriate dimensional tolerances are maintained during manufacturing. The required post-coating machining steps (such as grinding to meet surface finish requirements) are also expensive and time consuming, typically requiring diamond cutting tools and specialized operations. Such post-coating machining may also result in damage to the brake disc, such as via chipping or cracking of the newly deposited coating. This may not only adversely affect the structural integrity of the wear-resistant coating itself, but may also make the coating susceptible to intrusion by environmental contaminants, leading to problems such as flaking, wear, etc. as described above.
[0007] Compounding this problem is that many brake discs are perforated or otherwise provided with slots or grooves (axially). Such features provide pathways for brake wear material and water to accumulate and, due to the centrifugal forces generated during operation, drain outwardly along the grooves and away from the braking surface. Such features may therefore improve response behavior during wet weather and may also increase heat removal in the brake disc via increasing surface area, providing airflow (e.g., via through holes), etc. However, it will be appreciated from the above that such features are very limited in application to conventional protective coatings, are not easily machined or processed after application, and are therefore prohibited for use in contoured brake discs. Therefore, there is a need to provide additional solutions for resilient and cost-effective brake discs to meet the growing performance, manufacturing, and environmental safety demands of modern brake systems. Summary of the invention
[0008] A corrosion and wear resistant brake disc is provided. The brake disc includes a brake body having at least one braking surface, and a wear resistant coating electrodeposited on the braking surface. The wear resistant coating comprises a precipitation hardened cobalt-phosphorus (CoP) alloy and exhibits a Vickers hardness of about 900 HV to about 1050 HV. The wear resistant coating is optionally formulated with various additives to enhance and / or customize performance. In addition, the wear resistant coating exhibits both excellent wear resistance and corrosion resistance, excellent bond strength to a desired substrate material, and is applied via a method that allows post-deposition machining in a pre-hardened state.
[0009] A method for preparing a brake disc is also provided. The method includes electrodepositing a cobalt-phosphorus (CoP) alloy on a braking surface of a disc body to a thickness of typically at least about 150 μm to obtain a coated disc body. The method also includes heat treating the coated disc body to precipitation harden the CoP alloy and obtain a corrosion-resistant and wear-resistant coating on the braking surface. The coating exhibits a Vickers hardness of about 900 HV to about 1050 HV. The method optionally includes machining the coated disc body before heat treatment, wherein the precipitation-hardened CoP alloy of the corrosion-resistant and wear-resistant layer exhibits a Vickers hardness of at least twice the Vickers hardness of the deposited cobalt-phosphorus (CoP) alloy of the coated disc body (i.e., before heat treatment).
[0010] Various additional examples, aspects, and other useful features of embodiments of the present disclosure will also become apparent to those of ordinary skill in the relevant industry given the additional description provided below. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Color Drawings Available: The patent or application file associated with this disclosure in the United States Patent and Trademark Office contains at least one drawing executed in color. Copies of this patent or patent application publication with one or more color drawing(s) will be provided by the Office upon request and payment of the necessary fee.
[0012] At least one embodiment of the present invention will be described below in conjunction with the following drawings, wherein like numbers represent like elements, and:
[0013] Figure 1 shows an exemplary coated brake disc according to the present embodiment,
[0014] Figure 2 is an isometric cross-sectional view of a brake band of a coated brake disc protected by a corrosion- and wear-resistant coating according to the present embodiment;
[0015] Figure 3 Images showing the microstructure of the corrosion- and wear-resistant coatings on sample substrates prepared in Examples at 500x (a) and 5000x (b);
[0016] Figure 4 a series of images showing a corrosion and wear resistant coating after repeated thermal cycling simulating extreme braking events during operation; and
[0017] Figure 5 A series of images showing corrosion and wear resistant coatings after long term exposure to an extremely corrosive environment. DETAILED DESCRIPTION
[0018] The following detailed description is merely exemplary in nature and is not intended to limit the compositions or methods of use. Furthermore, there is no intention to be bound by any theory presented in the preceding background or the following detailed description.
[0019] A corrosion-resistant and wear-resistant brake disc and a method for preparing the same are provided herein. The brake disc comprises a brake body having at least one braking surface, and a corrosion-resistant and wear-resistant coating electrodeposited on the braking surface. The corrosion-resistant and wear-resistant coating comprises a precipitation-hardened cobalt-phosphorus (CoP) alloy and may optionally be formulated with various additives as described below. The corrosion-resistant and wear-resistant coating exhibits both excellent wear resistance and corrosion resistance and excellent bonding strength with the desired substrate material. The method allows for post-deposition machining of the coating and / or the brake body itself when the coating is in a pre-hardened state, thereby providing enhanced functionality and practicality for the improved coated brake disc. These and other features will be understood in light of the description and examples herein.
[0020] Generally speaking, the present disclosure provides a coating composition composition, a method for preparing and / or applying a coating composition to a substrate (e.g., forming a coating thereon), a method for preparing a multilayer coated product, and a coated product prepared by such an application method. For the sake of brevity, well-known conventional techniques related to compositions, methods, processes, equipment, systems, and products and their various parts and components may be introduced or otherwise described in different levels of description in the embodiments herein. For example, conventional techniques related to the formation of coating compositions may not be described in detail herein, because the various steps in the manufacture of such compositions are well-known, or have been previously described and provided in other ways, and therefore, in view of the embodiments and examples provided herein, those skilled in the art will readily understand and envision. Similarly, the various tasks and process steps described herein may be incorporated into a more comprehensive program or process, which has additional steps or functions not otherwise described, such as those known and understood by those skilled in the art. Such conventional steps may only be briefly mentioned or may be completely omitted without providing well-known process details. However, the scope of the description is not intended to limit the applicability of such conventional procedures, which may provide better and / or unexpected results when combined with the unique features of the embodiments provided herein.
[0021] It will be understood that the coated brake disc and the method for making the same are interrelated and, therefore, are best understood in light of one another. Likewise, unless expressly stated otherwise, the common ingredients, precursors, and final features of the products of the independently described methods and articles will be understood to be related to one another. In this way, the brake disc can be provided as an independent article, or otherwise provided as a by-product, as will be understood in light of the examples provided herein. In addition, it will be understood that the method does not rely on conventional techniques of high velocity oxygen fuel (HVOF), high velocity air fuel (HVAF), and / or kinetic metallization (KM) for material deposition, providing a corrosion-resistant and wear-resistant coating having unique properties that cannot be achieved by such conventional processes. These distinguishing features are introduced and described herein both qualitatively and quantitatively.
[0022] With reference to the accompanying drawings, Figure 1 1 . An exemplary brake disc 10 is shown in FIG. The brake disc 10 comprises a brake band 12 having two opposing braking surfaces (14a, 14b), each of which at least partially defines one of the two main faces of the brake disc 10. These braking surfaces 14a, 14b are provided with structural features, exemplified by holes 18, and the brake disc 10 as a whole is shown as internally ventilated. The brake disc 10 comprises a corrosion-resistant and wear-resistant coating indicated by 16. For simplicity, the coating 16 may be simply referred to as a "wear-resistant coating" 16, without limiting the scope of its function or properties.
[0023] Figure 2 , a schematic cross-sectional view of a portion of the brake band 12 is shown centered on one of the holes 18. The brake band 12 includes an underlying substrate or body 20 having a surface 14a on which the wear-resistant coating 16 is formed. The body 20 may have any number and type of structural features (such as holes 18 and / or grooves, channels, slots, etc.) that may exist prior to forming the wear-resistant coating 16 or may be defined via a machining operation performed during the coating process. Typically, the features exemplified by the holes 18 exist prior to the coating process such that the wear-resistant coating 16 covers the interior surface of the body 20, such as Figure 2 As shown, this provides maximum environmental barrier protection for the underlying body 20.
[0024] The wear-resistant coating 16 can be prepared as a single layer or multiple layers. Figure 2 As indicated by the dashed line 22, the wear-resistant coating 16 can be deposited as a first cobalt-phosphorus (CoP) alloy layer 24 and a subsequently deposited second CoP alloy layer 26. When so formed, the CoP alloy layers 24, 26 may have substantially equal thickness, morphology, and / or formulation or may not have substantially equal thickness, morphology, and / or formulation. For example, the first CoP alloy layer 24 can be electrodeposited on the component surface 14a using a first electroplating bath chemistry, and then the partially coated body 20 is removed from the electroplating bath, machined, and returned to the same or similar electroplating bath; and then the second CoP alloy layer 26 is coated on the first CoP alloy layer 24 via electrodeposition. As further discussed herein, such methods may be useful when the precipitation-hardened wear-resistant coating 16 is deposited at a relatively high thickness and may be prone to nodular growth. In such instances, nodular growth may occur near the edges, corners, and similar topological features (e.g., such as holes 18) of the body 20 as the electroplating process proceeds. Therefore, local irregularities or nodular protrusions develop, grow and potentially clear the plating current, hinder features with smaller sizes, and cause similar problems. As a more specific example, in an embodiment where the hole 18 exists before the coating formation process (as opposed to being formed after the coating formation process by drilling or other machining), local growth may occur near the mouth of the hole 18, and if not removed, it may pinch off or block the hole 18. Such situations can be avoided by temporarily stopping the plating process, grinding or otherwise removing such local growth areas, and then resuming the plating process. In other embodiments, the wear-resistant coating 16 can be deposited in three or more layers, and any number and type of machining operations are alternately performed with the layer deposition steps provided herein.
[0025] In addition to the wear resistant coating 16 , the brake disc 10 may be manufactured to include one or more additional layers. Figure 2 , which depicts a representative barrier layer 28 between the body 20 and the wear-resistant coating 16. The barrier layer 28 can be formulated to prevent or at least impede contaminants from penetrating through the thickness of the wear-resistant coating 16, for example to reduce corrosion or other degradation of the underlying body 20. However, one feature of the present embodiment is the ability to directly coat the body 20 without the need for such a barrier layer 28. In a typical embodiment, the brake disc 10 has no intermediate layer (e.g., barrier layer 28) between the body 20 (e.g., surface 14) and the wear-resistant coating 16. As shown in the examples, the methods and compositions of the wear-resistant coating 16 further described herein provide excellent bonding to the body 20 and barrier properties in terms of wear resistance and corrosion resistance.
[0026] Turning to the various components, it will be appreciated that the form of the brake disc 10 is not particularly limited and may be presented in a form suitable for use with an opposed piston type disc brake system or a floating type disc brake system, a mechanical or hydraulic system, etc., without limitation to a particular vehicle or configuration, as long as it is suitable for the practice of the embodiments presented herein. The superior properties of the wear resistant coating 16 provide a wide range of utility, enabling use on heavy transport vehicles as well as light consumer vehicles without performance limitations. Likewise, the brake band 12 may be flat, dimpled, drilled, grooved, or any combination thereof.
[0027] The brake disc 10 may be unitary in construction, or may alternatively be a multi-component assembly including a brake band 12. Generally, the brake band 12 is selected from readily available materials suitable for brake disc applications, such as gray cast iron, aluminum alloys, titanium alloys, and various combinations thereof. Other materials, such as steel, may also be employed. The brake band 12 may be a single composition (e.g., gray cast iron), or may alternatively be a composite material. In some embodiments, the brake band 12 is made entirely of gray cast iron. In some such embodiments, the entire body 20 consists essentially of gray cast iron.
[0028] As described above, the wear-resistant coating 16 comprises a precipitation-hardened cobalt-phosphorus (CoP) alloy. Generally, the wear-resistant coating 16 is formed by electrodepositing the CoP alloy onto a body in a pre-hardened state, followed by optional machining, and then heat treatment to precipitation-harden the CoP alloy and obtain the wear-resistant coating 16.
[0029] Prior to the deposition step, the surface 14 of the body 20 is typically prepared for coating, such as by cleaning (eg, washing, acid treatment to dissolve surface oxides, degreasing, etc.), grinding or polishing, or the like.
[0030] Electrodeposition of a CoP alloy (generally, electroplating body 20) typically includes providing a source of Co and P, such as via an electroplating bath containing an electrolyte composed of Co ions and P ions, such as in the form of a salt. Examples include cobalt sulfate, phosphorous acid, etc. As will be appreciated by those skilled in the art, additional acids, salts, and electrolytes may also be utilized to facilitate electroplating.
[0031] The CoP alloy typically contains about 8% to about 12% phosphorus (P) by weight (wt%). The P content throughout the alloy can vary, so that such values represent the average P content throughout the alloy. The balance of the CoP alloy is typically cobalt (Co). In some embodiments, the CoP alloy consists essentially of Co and P according to the above ratios. When the wear-resistant coating 16 is prepared by multiple independent depositions, the specific composition of the CoP alloy can vary between layers. In some embodiments, each layer of the independently deposited CoP alloy consists essentially of Co and P according to the above ratios. In other embodiments, as will be appreciated by those skilled in the art, the layers may be intentionally varied, for example for P content.
[0032] During electroplating, a cobalt source can be provided as a liquid additive, a powder additive and / or a soluble substance to provide a Co ion source during the electroplating process. Typically, Co ions are provided as water-soluble additives, such as Co sulfate (CoSO4.7*H2O). P ions can be provided using suitable chemicals as well, and in an embodiment, can be supplied by the decomposition of phosphorous acid (H3PO3) added to the electroplating solution. Electroplating bath chemicals can also be formulated to include other ingredients or components, including pH balance agents and / or chelating agents, such as organic acids. Other bath preparations are also possible, and other parameters (e.g., temperature and stirring intensity) are fine-tuned to be applicable to specific electroplating bath operations.
[0033] In some embodiments, the wear-resistant coating comprises one or more performance additives. For example, in certain embodiments, the coating comprises an anti-wear additive (i.e., an anti-wear component). Examples of suitable anti-wear additives include anti-wear particles, such as particles composed of ceramics, etc. Specific examples of anti-wear additives include particles of boron carbide (B4C), tungsten carbide (WC), titanium nitride (TiN), aluminum oxide (Al2O3), and combinations thereof. In a specific embodiment, the wear additive is selected from B4C particles and / or WC particles.
[0034] The total amount of anti-wear additive is generally about 10 volume percent to about 55 volume percent of the coating, such as about 15 volume percent to about 45 volume percent, or about 20 volume percent to about 40 volume percent, or about 20 volume percent to about 30 volume percent. As can be understood in view of the examples, the loading amount (i.e., volume %) of the anti-wear additive can be determined by cross-sectional analysis using a scanning electron microscope (SEM) combined with energy dispersive X-ray spectroscopy (EDX). More particularly, SEM-EDX can be used to provide an analytical image in which the two-dimensional (2D) area of the particles shown in the cross section represents the three-dimensional (3D) volume of the particles in the coating. Depending on the specific particles selected, this method can be used quantitatively or qualitatively, for example, controlling the distribution of particle size, shape, etc. can provide a more accurate correspondence between the 2D area and the 3D volume of the particles in the coating.
[0035] In a particular embodiment, the wear-resistant coating comprises B4C particles. Typically, the B4C particles are present in an amount of about 20% to about 40% by volume based on the total weight of the wear-resistant coating. Surprisingly, it was found that by keeping the particles suspended during the application process, B4C can be loaded in higher amounts than other anti-wear additives (e.g., WC), which increases the loading capacity and achieves a higher loading of the anti-wear additive.
[0036] In some embodiments, the wear-resistant coating further comprises a lubricant compound. Examples include hexagonal boron nitride (hBN), molybdenum disulfide (MoS2), tungsten disulfide (WS2), graphene, zirconium oxide, and combinations thereof. Such lubricant compounds can be used with anti-wear additives or used independently. Typically, the loadings of all additives used correspond to those described above for anti-wear additives.
[0037] In some embodiments, as described above, the B4C particles act both as an anti-wear additive and also as a lubricity additive.
[0038] It should be understood that the additives present in the coating may include different densities from one another, such that the weight percent (wt %) of any one or more of the additives in the coating may vary. For example, B4C has a density of about 2.5 g / cc, while WC has a density of about 15.63 g / cc, such that the equivalent particle loading expressed in volume % is different from the equivalent particle loading expressed in weight %. A specific weight % loading based on a particular particle may be utilized or determined, as will be understood by one skilled in the art.
[0039] CoP alloys are typically deposited to a minimum thickness of 100 μm. When machining is performed on CoP alloys, a minimum thickness of at least about 150 μm can be used to account for material loss. However, the wear-resistant coating 16 will work at a final thickness of about 40 μm to about 60 μm, so that a minimum deposition thickness of 100 μm can be used under normal circumstances. Generally speaking, a deposition thickness of 100 μm to 300 μm is utilized, (such as 150 μm to 200 μm). Thicknesses exceeding such a range, such as about 350 μm to about 500 μm, have also been successfully utilized. However, when the thickness is about 500 μm or thicker, additional attention to the heat treatment step is required to prevent cracking during cooling. Therefore, a typical embodiment utilizes a total thickness of the CoP alloy in the range of about 100 μm to about 500 μm, including all deposited layers. In some embodiments, the total thickness of the CoP alloy as deposited is maintained between about 150 μm and about 350 μm, or between about 150 μm and about 300 μm, or between about 150 μm and about 250 μm.
[0040] As described above, it should be understood that the electrodeposition method does not rely on conventional techniques of high velocity oxygen fuel (HVOF), high velocity air fuel (HVAF), and / or kinetic metallization (KM). More specifically, the method is typically free of (i.e., performed without) such techniques.
[0041] Once the CoP alloy is deposited, the coated disk body can be machined. Generally speaking, the precipitation-hardened CoP alloy of the wear-resistant layer exhibits a Vickers hardness that is at least twice that of the as-deposited cobalt-phosphorus (CoP) alloy prior to heat treatment. Therefore, the machining step prior to heat treatment provides many advantages in terms of ease of operation and maintaining the integrity of the coating and the underlying component body.
[0042] Generally speaking, conventional tools and processes can be used to machine the deposited CoP alloy, i.e., the CoP alloy in a pre-hardened or softened state. Typically, the CoP alloy has a relative hardness value of about, for example, 400 HV to 600 HV (such as 500 HV to 600 Hv). Machining operations can be performed to define detailed structural features in the body 20 as desired. For example, in some embodiments, mechanical drilling, laser drilling, water jetting, electrical discharge machining, etc. can be performed to form channels, slots, grooves, or holes, such as Figure 1 These are shown in 14.
[0043] Additionally or alternatively, grinding or polishing may be performed to impart a highly smooth surface finish to the coating surface, such as a surface finish having an average roughness of less than 0.4 microns (approximately 15 μm) RA.Such process steps may be repeated as desired until the desired alloy body thickness is achieved.
[0044] Once machining of the coated disk body is complete, a heat treatment is performed to precipitation harden the CoP alloy and obtain a wear-resistant coating. In some embodiments, the body 20 is advantageously annealed (e.g., as may be the case of a cold-worked metal or alloy such as steel), and a single heat treatment process may be performed to precipitation harden the CoP alloy while annealing the disk body. However, typically, the heat treatment is only to precipitation harden the CoP alloy to form a wear-resistant coating.
[0045] The specific parameters of the heating schedule will vary depending on the composition of the CoP alloy itself. Typically, the heat treatment is performed at a peak temperature of 250°C to 450°C for a period of 2 hours to 24 hours. After heat treatment and precipitation hardening, the wear-resistant coating typically exhibits a Vickers hardness of at least about 900 HV to about 1050 HV.
[0046] The specific configuration of the brake disc can be selected in view of the desired end use. For example, in view of the intended use of the brake disc, the specific particles and / or the specific load used can be selected, and the coating thickness and other parameters can also be selected. For example, in high wear applications (such as in heavy commercial vehicles), the brake disc can be configured with a thicker coating and / or a higher anti-wear particle load. In some embodiments, the wear-resistant coating is suitable for coating to a thickness of at least 150 μm, contains about 20% to about 40% by volume of B4C anti-wear particles, and passes 3000 revolutions, or passes 6000 revolutions of ASTM G65-16 (2021) test.
[0047] Additional parameters and features of the exemplary embodiment wear resistant coating 16 and coated brake disc will be further understood in view of the following examples.
[0048] Example
[0049] General coating procedure:
[0050] The substrate was electroplated using a bath of cobalt sulfate, phosphoric acid, boric acid and optionally anti-wear and / or lubricating additives (e.g. B4C) to obtain a 200 μm (target; actual 180 μm to 190 μm) CoP alloy layer with a phosphorus content of 8 to 12 wt% based on the total weight of the CoP alloy.
[0051] The hardness is measured via a microhardness indenter. The CoP alloy layer achieves a hardness of 400 to 600 HV. The coated substrate is then heat treated (250 to 450° C.; 2 to 24 hours) to obtain a hardness of 900 to about 1050 HV.
[0052] Cross-sectional analysis was performed using a scanning electron microscope (SEM) with a backscatter detector in conjunction with energy dispersive X-ray spectroscopy (EDX) to evaluate and monitor compositional changes during the following performance examples. When utilized, the B4C particles in the coating matrix were also evaluated and monitored via SEM-EX, where the B4C particle content, representing the approximate volume % of B4C in the CoP matrix, was estimated by calculating the 2D area % of the B4C particles (shown as dark flakes in the light-colored CoP matrix).
[0053] High temperature cycle performance
[0054] High temperature cycle evaluations are performed to simulate repeated braking, such as downhill and / or under load. Extreme temperatures (500°C) and a large number of continuous cycles are selected to demonstrate performance under extreme conditions.
[0055] Sample coupons (4140 carbon steel) were plated according to the general procedure described above to a coating thickness of 180 μm to 190 μm. Small coupons were used to facilitate rapid heating / cooling during repeated cycles.
[0056] SEM-EDX analysis ( Figure 3 , a=500x, b=5000x) shows a uniform coating structure with a B4C particle (dark flake) content of 40% to 45%.
[0057] The samples were equipped with inserted thermocouples for monitoring the actual sample (coating) temperature during cycling to ensure that the material achieved the target temperature for the target duration.
[0058] The box furnace (air) is prepared for long soaks. The quartz tube furnace (air) is prepared for short soaks. The furnace hot zone is set to 200°C above the set point (e.g. 700°C) to achieve a high heating rate and ensure that the set point (500°C) is reached. Cooling is performed under ambient conditions to reach room temperature (RT) before starting the next cycle.
[0059] In each case, the sample was inserted into the hot zone until the actual sample temperature (thermocouple) reached the set point. The sample was then held for 10 seconds, removed from the furnace, and cooled to room temperature to complete one cycle. The lowest temperature achieved at the beginning of each hold was 500°C; the highest temperatures were 540°C to 560°C. The samples exhibited Newtonian cooling, with a rapid drop in temperature within the first few hundred degrees, and each sample required a cooling time of 15 to 20 minutes to reach a touch-safe temperature (30 to 50°C based on the thermocouple).
[0060] Each sample was subjected to 50 cycles at a set point of 500° C. After every 10 cycles, the hardness was measured by SEM-EDX analysis to monitor the physical changes.
[0061] The results of the hardness tests are shown in Table 1 below, where each value is reported as an average of 5 measurements. Figure 4 Images from SEM-EDX analysis are shown.
[0062] Table 1. Hardness (HV) measurement results during high temperature cycling
[0063]
[0064] The wear resistant coating was unchanged after the high temperature cycling event. As shown in the figure, no physical changes were observed after cyclic exposure to elevated temperatures. No significant changes in hardness were observed. No changes in the microstructure of the coating were observed via SEM-EDX. The wear resistant coating exhibited excellent temperature stability.
[0065] Corrosion resistance
[0066] Long-term constant exposure corrosion evaluations are performed to assess corrosion resistance. Salt immersion tests are prepared to simulate environmental conditions. Specifically, conditions are selected to simulate longer hours in salt spray to provide corrosion resistance performance results under extreme environmental conditions.
[0067] The sample panels (4140 carbon steel) were plated on one face and the other face / sides were masked with yellow Kapton tape (fixed with epoxy). The samples were placed face down on a circular stand to cure. In some instances, the epoxy dripped down the stand onto the panel face, visible as a circular mark of epoxy.
[0068] A saline bath was prepared with NaCl at a concentration of 75 g / L and the pH was adjusted with HCl to a pH of 2.5. Air was bubbled through the saline during the test.
[0069] Corrosion testing was performed via immersion in a salt water bath. Evaluations were performed in duplicate at RT and 50°C. The elevated temperature was chosen to provide an aggressive corrosion environment with faster kinetics than the RT evaluation. Under the chosen conditions, 7 days immersion is equivalent to 1000 hours in salt spray. The samples were immersed for a total of 14 days (2000 hours salt spray equivalent).
[0070] The results of the analysis are shown in Table 2 below. A "pass" was recorded when no rust was evident by visual observation. A "fail" was recorded when rust was observed upon inspection. Images of the panels before immersion, after 7 days in the salt bath, and after 14 days in the salt bath are shown in Table 2. Figure 5 middle.
[0071] Table 2. Corrosion test results
[0072]
[0073] The wear resistant coating does not change after long-term exposure to a highly corrosive environment. As shown, no rusting, pitting or flaking was observed, even on samples immersed in elevated temperatures.
[0074] Ring Shear Adhesion Test: Bond Strength
[0075] Cylindrical rods are prepared via the process evaluated, electroplated to a thickness of about 1.5 mm. The rods are machined in a manner to remove all electroplated deposits, except for a small electroplated ring (about 1.5 mm wide, about 2.5 cm apart) of a predetermined width. The rods are then cut between the electroplated rings. These parts of the rods with electroplated rings are tested by forcing the rods to pass through a hardened steel die having a hole with a diameter greater than the diameter of the rod but less than the diameter of the rod and the coating. The load and coating area required to cause failure are used to calculate the bond strength, as described by JW Dini et al., "Techniques for Quantitatively Measuring Adhesion of Coatings", Metal Finishing, 75.42 (March 1977) and 75,48 (April 1977).
[0076] Comparative Analysis: Coefficient of Friction (COF), GCI Compatibility and Bond Strength
[0077] The wear resistant coating (CoP-WRC) of the present embodiment was evaluated for coefficient of friction (COE), coefficient of thermal expansion (CTE) and bonding strength (ring shear adhesion) against comparative hard chrome (electroplating) and WC HVOF (86 / 10 / 4) coatings. The results of these evaluations are set forth in Table 3 below.
[0078] Table 3. COE, COF, CTE and bonding strength results
[0079]
[0080] The wear resistant coatings exhibit lower COF than the comparative chrome or HVOF coatings, where COF is comparable to GCI. It is believed that the introduction of lubricating additives in the electroplating slurry will further reduce the COE of the wear resistant coatings, thereby providing an improvement in GCI.
[0081] Wear resistant coatings are highly compatible with GCI in terms of low CTE mismatch. Brake components are subject to extreme thermal shock during normal operation. Since higher CTE mismatch increases the potential for spalling / delamination, it is believed that wear resistant coatings provide unique benefits over comparative coatings when applied to GCI brake discs.
[0082] The wear-resistant coating has a very high bond strength compared to comparable chrome or HVOF coatings, providing excellent adhesion and coating stability that brake discs are subjected to in everyday operation.
[0083] Although at least one exemplary embodiment has been presented in the aforementioned specific embodiments, it should be understood that there are a large number of variations. It should also be understood that an exemplary embodiment or multiple exemplary embodiments are only examples and are not intended to limit the scope, applicability or configuration in any way. On the contrary, the aforementioned specific embodiments will provide a convenient roadmap for realizing exemplary embodiments for those skilled in the art. It should be understood that, without departing from the scope as set forth in the attached claims, various changes may be made to the functions and arrangements of the elements described in the above exemplary embodiments. In addition, all combinations of the above-mentioned components, compositions, method steps, formulation steps, etc. are hereby explicitly intended to be used in various non-limiting embodiments, even if such combinations are not explicitly described in the same or similar paragraphs.
[0084] For any Markush group relied upon for specific features or aspects of various embodiments described herein, different, specific and / or unexpected results may be obtained from each member of the corresponding Markush group independent of all other Markush members. Each member of the Markush group may be relied upon individually and / or in combination and provides adequate support for specific embodiments within the scope of the appended claims.
[0085] In addition, any ranges and subranges relied upon in describing various embodiments of the present invention fall within the scope of the appended claims independently and collectively, and are understood to describe and contemplate all ranges including integer values and / or fractional values therein, even if these values are not explicitly written herein. It is readily recognized by those skilled in the art that the ranges and subranges listed here fully describe and enable various embodiments of the present invention, and that these ranges and subranges may be further described as associated halves, thirds, quarters, fifths, etc. As just one example, the range of "0.1 to 0.9" may be further described as a lower third, i.e., 0.1 to 0.3, a middle third, i.e., 0.4 to 0.6, and an upper third, i.e., 0.7 to 0.9, which are individually and collectively within the scope of the appended claims and may be relied upon individually and / or collectively, and provide sufficient support for specific embodiments within the scope of the appended claims. In addition, for language defining or modifying ranges, such as "at least", "greater than", "less than", "not greater than", etc., it is understood that such language includes subranges and / or upper or lower limits. As another example, a range of "at least 10" inherently includes a subrange of at least 10 to 35, a subrange of at least 10 to 25, a subrange of 25 to 35, etc., and each subrange can be relied upon individually and / or collectively, and provides sufficient support for specific embodiments within the scope of the appended claims. Single numbers within the disclosed ranges can be relied upon, and provide sufficient support for specific embodiments within the scope of the appended claims. For example, a range of "1 to 9" includes various single integers (such as 3), as well as single numbers including decimal points (or fractions) (such as 4.1), which can be relied upon, and provide sufficient support for specific embodiments within the scope of the appended claims. Finally, it should be understood that the term "about" with respect to any specific numerical values and ranges described herein is used to represent values within standard deviations, equivalent functions, efficacies, final loads, etc., as understood by those skilled in the art, using relevant conventional techniques and methods to formulate and / or utilize compounds and compositions such as those described herein. Thus, the term "about" can mean a value within 10%, or within 5%, or within 1%, or within 0.5%, or within 0.1% of a recited value or range.
[0086] Although the present disclosure has been described with respect to particular embodiments thereof, it is evident that many other forms and modifications will be apparent to those skilled in the art. The appended claims and the present disclosure should generally be construed to cover all such obvious forms and modifications, which are within the true scope of the present disclosure.
Claims
1. A brake disc, comprising: a disc body having at least one braking surface; and a corrosion-resistant and wear-resistant coating electrodeposited on said at least one braking surface, The corrosion- and wear-resistant coating comprises a precipitation-hardened cobalt-phosphorus (CoP) alloy and exhibits a Vickers hardness of 900 HV to 1050 HV.
2. The brake disc of claim 1, wherein the disc body comprises a base material selected from the group consisting of: (i) gray cast iron; (ii) aluminum alloy; (iii) titanium alloy; and (iv) any combination of (i) to (iii). 3 . The brake disc according to claim 1 , wherein the CoP alloy of the corrosion- and wear-resistant coating has a phosphorus content of 8 to 12 wt %, based on the total weight of the CoP alloy.
4. The brake disc according to claim 1, wherein the corrosion- and wear-resistant coating further comprises 10 to 55 volume % of wear-resistant particles selected from the group consisting of: (i) boron carbide (B4C); (ii) tungsten carbide (WC); (iii) titanium nitride (TiN); (iv) aluminum oxide (Al2O3); or (v) Any combination of (i) to (iv).
5. The brake disc of claim 1, wherein the corrosion- and wear-resistant coating further comprises a lubricant compound selected from the group consisting of: (i) hexagonal boron nitride (hBN); (ii) molybdenum disulfide (MoS2); (iii) tungsten disulfide (WS2); (iv) graphene; (v) zirconium oxide; and (vi) Any combination of (i) to (v).
6. A brake disc according to any one of claims 1 to 5, wherein the corrosion and wear resistant coating: (i) has an average thickness of 100 μm to 500 μm; (ii) retains a Vickers hardness of at least 90% of the initial Vickers hardness through at least 50 cycles of heating to at least 500°C and holding at at least 500°C, each cycle lasting for a period of at least 5 seconds; (iii) exhibits substantially no corrosion when immersed in salt water at a temperature of at least 50°C for at least 14 days; (iv) exhibits a bond strength to the braking surface of the body of at least 60 Ksi; (v) exhibits a coefficient of friction less than 0.35; or (vi) any combination of (i) to (v).
7. A method for preparing a brake disc according to claim 1, the method comprising: providing said disc body having at least one braking surface; electrodepositing a cobalt-phosphorus (CoP) alloy on the at least one braking surface to a thickness of at least 150 μm to obtain a coated disc body; as well as The coated disc body is heat-treated to precipitation harden the CoP alloy and form the corrosion-resistant and wear-resistant coating layer and thereby obtain the brake disc.
8. The method of claim 7, wherein the electrodeposition is performed without any high velocity oxygen fuel (HVOF) technique, high velocity air fuel (HVAF) technique or kinetic metallization (KM) technique; wherein the precipitation hardened CoP alloy of the corrosion and wear resistant coating exhibits a Vickers hardness at least twice that of the as-deposited cobalt-phosphorus (CoP) alloy before the heat treatment; and wherein the method optionally includes a step of machining the as-deposited cobalt-phosphorus (CoP) alloy of the coated disk body prior to the step of heat treatment.
9. The method according to claim 7, wherein: (i) the disk body comprises a base material selected from the group consisting of gray cast iron, aluminum alloy, titanium alloy, and combinations thereof; (ii) the cobalt-phosphorus (CoP) alloy deposited on the at least one braking surface has a phosphorus content of 8 wt % to 12 wt % based on the total weight of the CoP alloy; (iii) the corrosion- and wear-resistant coating further comprises 10 vol % to 55 vol % of wear-resistant particles selected from the group consisting of boron carbide (B4C), tungsten carbide (WC), titanium nitride (TiN), aluminum oxide (Al2O3), and combinations thereof; (iv) the corrosion- and wear-resistant coating further comprises a lubricant compound selected from the group consisting of hexagonal boron nitride (hBN), molybdenum disulfide (MoS2), tungsten disulfide (WS2), graphene, zirconium oxide, and combinations thereof; or any combination of (v)(i) to (iv).
10. The method of any one of claims 7 to 9, wherein the corrosion and wear resistant coating: (i) has an average thickness of 100 μm to 500 μm; (ii) maintains a Vickers hardness of at least 90% of the initial Vickers hardness through at least 50 cycles of heating to at least 500°C and holding at least 500°C, each cycle lasting at least 5 seconds; (iii) exhibits substantially no corrosion when immersed in salt water at a temperature of at least 50°C for at least 14 days; (iv) exhibits a bond strength with the braking surface of the body of at least 60 Ksi; (v) exhibits a coefficient of friction less than 0.35; or (vi) any combination of (i) to (v).